(3MdHI GdcejJs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s ((3eMeO Hf CHh HcQ GdaQG s)
(3ChdgG (B:s
(3GdMeO ddg GdPi COGQ cDhS GdCOH Ydi Cgd GdCOH aeGdhG WQHkG HbghI GdEfTGA hHYO abO SCdfi ef CeQg eWGY CHQRJ ai hUa GdcejJ s
(3BNQgG (B:s
(3hdjS GYJbGO GdeQA eG NW cag ceG Cf MGcI GdcaQ djS HcGaQ hUdi Gddg Ydi SjOfG eMeO hGdg hUMHg hSde hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs